Sweden : 2015 Article IV Consultation-Press Release; Staff Report; Information Annex; and Statement by the Executive Director for Sweden. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that Sweden's economy is performing well, with real GDP growth of 3.4 percent per year in the first three quarters of 2015, up from 2.3 percent in 2014. Job creation was robust in the first three quarters of 2015, helping bring the unemployment rate down to 7.2 percent in the third quarter. Core inflation rose to 1.4 percent per year on average in recent months, but remains below the 2 percent target. Solid growth of about 3 percent is expected to continue into 2016.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet